How far the Course Review Horay (CRH) model and flashcard enhance scientific attitude and science literacy in fourth-grade force learning? - Ni Made Supriani; Ketut Suma; I Nyoman Jampel (Psychology, Evaluation, and Technology in Educational Research, 2025)
This study aims to analyze the effect of the Course Review Horay (CRH) Model assisted by Flashcards on developing students' Scientific Literacy (SL) and Scientific Attitude (SA) in Grade IV at elementary school Cluster III, Negara, Bali. Focusing on the Force Chapter, aligned with the demands of Merdeka Curriculum's Deep Learning. Employing a Nonequivalent Pre-test Post-test Control Group Design and a Mixed Methods approach, the research involved 90 students. Quantitative results demonstrated a significant effect on both variables, with increases categorized as moderate to high (T-test). Qualitative analysis indicated that the synergy between the CRH syntax and Flashcards effectively overcomes the conceptual difficulties of the abstract Force material. Flashcards functioned as Visual Concretization of Force Causality, accelerating SL comprehension on PISA indicators. Meanwhile, the competitive Horay! aspect effectively cultivated SA, characterized by Accelerated Decision Making and Internalization of Evidence Through Consensus within the group. The conclusion shows that this model is effective and coherent in bridging students' cognitive and affective dimensions, providing a strong pedagogical contribution to primary level natural and social science learning.